2022
DOI: 10.3390/md20070462
|View full text |Cite
|
Sign up to set email alerts
|

Connection of Isolated Stereoclusters by Combining 13C-RCSA, RDC, and J-Based Configurational Analyses and Structural Revision of a Tetraprenyltoluquinol Chromane Meroterpenoid from Sargassum muticum

Abstract: The seaweed Sargassum muticum, collected on the southern coast of Galicia, yielded a tetraprenyltoluquinol chromane meroditerpene compound known as 1b, whose structure is revised. The relative configuration of 1b was determined by J-based configurational methodology combined with an iJ/DP4 statistical analysis and further confirmed by measuring two anisotropic properties: carbon residual chemical shift anisotropies (13C-RCSAs) and one-bond 1H-13C residual dipolar couplings (1DCH-RDCs). The absolute configurati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
(120 reference statements)
0
5
0
Order By: Relevance
“…Among them, compounds 167-171 share the same trans-fused carbon skeleton, marking the first report of such a structure in the Sargassaceae family [63]. Compounds 172 and 173 also possess the same trans-fused bicyclic system and were found to exhibit photodamage attenuation effects [89,90]. Compounds 168, 169, and 171 showed antifouling activities against the settlement of certain macroalgae, the growth of microalgae, and the activities of mussels [63].…”
Section: Chromenesmentioning
confidence: 96%
See 2 more Smart Citations
“…Among them, compounds 167-171 share the same trans-fused carbon skeleton, marking the first report of such a structure in the Sargassaceae family [63]. Compounds 172 and 173 also possess the same trans-fused bicyclic system and were found to exhibit photodamage attenuation effects [89,90]. Compounds 168, 169, and 171 showed antifouling activities against the settlement of certain macroalgae, the growth of microalgae, and the activities of mussels [63].…”
Section: Chromenesmentioning
confidence: 96%
“…Two novel chromene meroditerpenoid isomers (167 and 168) and their derivatives (169-171), together with two new chromane meroditerpenoid epimers (172 and 173), were isolated from the brown alga C. baccata and S. muticum [63,[87][88][89]. Among them, compounds 167-171 share the same trans-fused carbon skeleton, marking the first report of such a structure in the Sargassaceae family [63].…”
Section: Chromenesmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, it should be mandatory that these δ H and δ C values should be provided within 0.001 and 0.01 ppm because this affects the precision of δ X data reported. The authors of [125] provide a positive example here. Unfortunately, in many of the articles cited above and recently published, such δ X data do not appear at all [23,29,30,58,[126][127][128].…”
Section: Ppm Respectively)mentioning
confidence: 99%
“…348 The structure of a tetraprenylated chromane has been revised to 883 following in-depth J-based configurational analysis coupled with comparison of experimental and calculated chiro-optical properties. 349 A seasonal study of the volatilome of both fresh and dried Croatian Dictyota dichotoma has indicated that the main volatile components are short chain lipids or are diterpenoid in origin, with distinct variation throughout the months of the study facilitating statistical differentiation of the sample treatments. 350…”
Section: Brown Algaementioning
confidence: 99%